2006
DOI: 10.1523/jneurosci.5160-05.2006
|View full text |Cite
|
Sign up to set email alerts
|

Kinematic and Electromyographic Study of the Nociceptive Withdrawal Reflex in the Upper Limbs during Rest and Movement

Abstract: This study set out to evaluate nociceptive withdrawal reflex (NWR) excitability and the corresponding mechanical response in the upper limbs during rest and movement. We used a three-dimensional motion analysis system and a surface EMG system to record, in 10 healthy subjects, the NWR in eight upper limb muscles and the corresponding mechanical response in two experimental conditions: rest and movement (reaching for, picking up, and moving a cylinder). The NWR was elicited through stimulation of the index fing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
42
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(46 citation statements)
references
References 56 publications
4
42
0
Order By: Relevance
“…We used the same electrical stimulation technique reported elsewhere (Don et al., 2008; Serrao et al., 2006). In brief, using ring electrodes, we stimulated the digital branch of the median nerve supplying the index finger.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We used the same electrical stimulation technique reported elsewhere (Don et al., 2008; Serrao et al., 2006). In brief, using ring electrodes, we stimulated the digital branch of the median nerve supplying the index finger.…”
Section: Methodsmentioning
confidence: 99%
“…The mean of the EMG area plus 2  SD , calculated in the prestimulus interval, was used as a threshold to determine the presence (denoted by a value above the threshold) or absence (a value below the threshold) of the NWR in the poststimulus interval in each trial. The NWR‐related EMG responses were measured as the difference between the EMG areas in the post‐ versus the prestimulus intervals for each examined muscle (Don et al., 2008; Serrao et al., 2006). …”
Section: Methodsmentioning
confidence: 99%
“…Phases divided on the basis of the velocity trajectory, which is bell-shaped5 ) , might be related to the phasic drives of the muscles’ activities. The peak of the velocity profile was reported to divide the reaching movement into a hand acceleration phase (positive values of tangential acceleration) and a hand deceleration phase (negative values of acceleration)9, 17 ) . The present study showed that this hand acceleration phase is composed of Phases IA and DA.…”
Section: Discussionmentioning
confidence: 99%
“…With regard to the upper limb, we recently reported that, during reaching and grasping movements, the excitatory component of the WR undergoes state‐ and phase‐dependent modulation according to the mechanical function exerted by each muscle in the course of the motor sequence. In particular, we observed that the amount and direction of the motion occurring at each joint in the course of the motor task were the main factors determining the presence of either a reflex reversal or a co‐presence pattern (Serrao et al. , 2006).…”
Section: Introductionmentioning
confidence: 99%